2008
DOI: 10.1002/jmor.10708
|View full text |Cite
|
Sign up to set email alerts
|

Stereological estimation of the surface area and oxygen diffusing capacity of the respiratory stomach of the air‐breathing armored catfish Pterygoplichthys anisitsi (Teleostei: Loricariidae)

Abstract: The stomach of Pterygoplichthys anisitsi has a thin, translucent wall and a simple squamous epithelium with an underlying dense capillary network. In the cardiac and pyloric regions, most cells have short microvilli distributed throughout the cell surface and their edges are characterized by short, densely packed microvilli. The mucosal layer of the stomach has two types of pavement epithelial cells that are similar to those in the aerial respiratory organs. Type 1 pavement epithelial cells, resembling the Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 31 publications
0
20
0
2
Order By: Relevance
“…These factors make the fish easily accessible for ecotoxicological studies. P. anisitsi have accessory air-breathing mechanisms (Cruz et al 2009) and when they rise to the surface to breathe they make contact with the diesel-insoluble portion. Thus, despite the fish's benthic habit, diesel oil at the doses tested was able to generate oxidative stress and affect the fish's metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors make the fish easily accessible for ecotoxicological studies. P. anisitsi have accessory air-breathing mechanisms (Cruz et al 2009) and when they rise to the surface to breathe they make contact with the diesel-insoluble portion. Thus, despite the fish's benthic habit, diesel oil at the doses tested was able to generate oxidative stress and affect the fish's metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on benthic animals can provide important data on differential responses of organisms to pollutants in different aquatic matrices. Pterygoplichthys anisitsi is a benthic armored catfish (Loricariidae) found in fresh waters of South America throughout the Uruguay, Paraguay, and Paraná River basins, where it inhabits water bodies characterized by low oxygen concentrations (Cruz et al 2009). This South American endemic species has not been used in ecotoxicological studies, and data generated from it could be of great importance for research on biomonitoring benthic freshwater environments in South America.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps this amount is not reflective of the amount of food the fish are capable of eating, and need to consume, to meet their energetic and nitrogen requirements. Moreover, corn gluten meal, although appropriate for tilapia, which possess an acidic stomach, may not be digested as efficiently by P. disjunctivus, which lacks a gastric stomach (da Cruz et al 2009;German 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors report the complete absence of digestive glands in the ABO stomach of loricariids (Carter, ; Oliveira et al , ). Surfactant‐producing lamellar bodies have also been documented in the stomach epithelial cells and gastric glands of Ancistrus (Satora & Winnicki, ), Hypostomus (Podkowa & Goniakowska‐Witalińska, ) and Pterygoplichthys (Cruz et al , ).…”
Section: Morphological Indicators Of the Gut As An Abomentioning
confidence: 99%
“…The ranges reported fall within those of other fish non‐gut ABOs and are in the range of mammalian lung diffusive distances (Weibel, ). Capillary densities of gut ABOs are typical for fish ABOs in general (Podkowa & Goniakowska‐Witalińska, , ; Cruz et al , ). Cruz et al () found the diffusing capacity of the Pterygoplichthys (Loricariidae) stomach ABO to be higher than for most other fish ABOs, but lower than published values for the lungs of the South American lungfish Lepidosiren paradoxa Fitzinger 1837 and the marbled lungfish Protopterus aethiopicus Heckel 1851 and substantially below estimates for lungs of same‐sized mammals (Weibel, ).…”
Section: Circulatory Modifications Associated With Gut Abo Evolutionmentioning
confidence: 99%